Brain Arteriovenous Malformations : Pathogenesis, Epidemiology, Diagnosis, Treatment and Outcome - Beneš, Vladimír; Bradáč, Ondřej (Springer International Publishing : Imprint: Springer, 2017)
This book reviews the natural course of arteriovenous malformation (AVM) disease and the active treatment modalities. These are compared with surgical and neuropsychological results achieved at the Military University Hospital, Prague, Czech Republic. Based on these comparisons, treatment recommendation for AVM is articulated. Furthermore, the long-term efficacy of different treatment is discussed. This book is written by an international group of European authors, and is aimed at neurovascular surgeons and neurosurgical residents.
Keywords: Medicine.; Neurosurgery.; Vascular surgery.; elektronické knihy; electronic books